PENATALAKSANAAN PSIKOGERIATRI DI UPT PELAYANAN SOSIAL TRESNA WERDHA HUSNUL KHOTIMAH PEKANBARU - Tesha Hestyana Sari; Rusherina Rusherina; Kurniawati Kurniawati (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
The increase in the number of elderly also causes various problems in today's life. Some of these problems include the decreased level of independence of the elderly due to a decline in body, psychological and social functions. Not all of the elderly live with their families or children. Some of the elderly have to live in a nursing home like at UPT. Tresna Werdha Husnul Khotimah Social Services Pekanbaru. The elderly who are in nursing homes are not all healthy. Some of the elderly have diseases such as hypertension. Gastritis, post stroke, hallucinations, social isolation, schizophrenia and others. Panti Werdha Khusnul Khotimah Pekanbaru has made a schedule of activities so that the elderly can still be active in the Panti Werdha environment. The orphanage has a weekly schedule such as religious lectures, making skills, social guidance, health checks, wirid and gymnastics. However, not all of the elderly participated in these activities. Based on these data, it can be seen that the elderly who are in nursing homes have health problems, both physically and psychologically. The general purpose of this community service activity is to carry out community service in the form of psychogeriatric management in the form of Brain Gym, Art Therapy and Reminiscence Therapy. The implementation method is in the form of direct practice. The achievements of this activity are the implementation of community service activities, cognitive improvement in the elderly and the absence of elderly people who have signs and symptoms of depression. The recommendation from the results of this activity is that there should be participation from the Panti management so that this activity can be carried out by trained therapists so that this activity can be sustainable.